Associations Between Biodiversity, Forest Characteristics, Distance to Blue Space and Accelerometer-Measured Physical Activity - Northern Finland Birth Cohort 1966 Study - Kangas, Katja; Pyky, Riitta; Tarvainen, Oili; Puhakka, Soile; Karhu, Jouni; Kangas, Maarit; Tolvanen, Anne; Korpelainen, Raija; Lankila, Tiina (Taylor & Francis, 2024)
We studied how the quantity and quality of residential green spaces and distance to different types of blue spaces are associated with the accelerometer-measured physical activity (PA) among adults with different levels of total daily PA. The associations of the participants’ socio-demographic and personal characteristics and environmental features with light PA (LPA) and moderate-to-vigorous PA (MVPA) were analyzed using linear mixed models (n = 5470). The results indicated that greater residential forest area was associated with higher LPA among those with high level of total daily PA and with less MVPA among those with low level of total daily PA. Environments with high tree stand structure diversity or close to sea were associated with higher MVPA in high PA group. Varied natural environment can encourage leisure time activities in nearby nature, but individuals’ personal and socioeconomic variables seemed to be more strongly associated with LPA and MVPA than environmental characteristics.
Keywords: accelerometer-measuredphysical activity; biodiversity; blue space; cohort study; forest characteristics